Local Diagnostic Reference Levels for X-Ray Examinations in an Australian Tertiary Hospital - Ng, Curtise; Sun, Zhonghua; Parry, H.; Burrage, J. (American Scientific Publishers, 2014)
Introduction: The use of diagnostic reference levels (DRLs) has been recommended by the International Commission on Radiological Protection (ICRP) since 1996. However, the national DRLs normally focus on the most common radiological examinations. The purpose of this study was to conduct a patient dose survey within an Australian tertiary hospital for proposing local DRLs for a wider range of (common) X-ray examinations. Methods: This survey was conducted retrospectively in one of the Australian largest hospitals. A tailored computer system was used to retrieve digital radiography images of adult outpatients taken within a period of one year from the hospital's picture archiving and communication system and their dose-related digital imaging and communication in medicine data was extracted for automatic dose analysis. Descriptive statistics were used to summarise the kerma-area product (KAP) and exposure factor distributions for comparison with the literature. Results: A total of 27,311 KAP values were collected from 59 (common) general X-ray projections. Nearly all third quartile (Q3) values of KAP for the most common projections (82%) were up to 87.6% lower than the national DRLs from various countries and European Commission. However, most of the median kV (71%) and nearly half of the median source-to-image distances (46%) were in the ranges of 3–22% and 2–18% lower than the reference values respectively. Conclusion: The local DRLs for 59 (common) X-ray projections were proposed based on the Q3 values of KAP for patient dose optimisation.